The effect of surgical approach on the histologyof the femoral head following resurfacing of the hip: Analysis of retrieval specimens. Issue 9 (September 2013) - Amarasekera, H. W.; Campbell, P. C.; Parsons, N.; Achten, J.; Masters, J.; Griffin, D. R.; Costa, M. L.
Abstract : Objectives: We aimed to determine the effect of surgical approach on the histology of the femoral head following resurfacing of the hip. Methods: We performed a histological assessment of the bone under the femoral component taken from retrieval specimens of patients having revision surgery following resurfacing of the hip. We compared the number of empty lacunae in specimens from patients who had originally had a posterior surgical approach with the number in patients having alternative surgical approaches. Results: We found a statistically significant increase in the percentage of empty lacunae in retrieval specimens from patients who had the posterior approach compared with other surgical approaches (p < 0.001). Conclusions: This indicates that the vascular compromise that occurs during the posterior surgical approach does have long-term effects on the bone of the femoral head, even if it does not cause overt avascular necrosis. Cite this article: Bone Joint Res 2013;2:200–5.